Flood frequency analysis between annual maximum series (AM) and peaks-over-threshold (POT) series in Selangor, Malaysia - Ooi, Zu Yan (2025)
Flood Frequency Analysis (FFA) refers to a statistical approach for estimating the probability and magnitude of flood occurrences. Annual Maximum (AM) is the most applied approaches in FFA, it focuses on the most extreme event during the period of time. In fact, it is also crucial to take both smaller and frequent flood events into consideration when performing flood frequency analysis. Therefore, another approach named Peaks-Over-Threshold (POT) method provides a more precise way of computing occurrences of floods by including noteworthy high flow events (even if they are not the most extreme of the year), but it is usually underemployed because of its complexities in threshold selection. This research attempts to compare these two approaches in the flood frequency analysis inb Selangor. This study employs the L-moment approach to estimate the parameters of three candidate distributions, which are the generalised Pareto (GPA) distribution, the generalised extreme value (GEV) distribution, and the generalised logistic (GLO) distribution. Then, the L-moment diagram will be implemented to ascertain the optimum distribution for the data series. Additionally, each data series' distribution performance will be evaluated using the goodness-of-fit test and efficiency assessments, namely mean absolute error (MAE), root mean square error (RMSE) and BIAS. This study aims to determine whether the AM or POT technique associated with one of the three distributions above yields a more dependable and accurate estimate of flood frequency in Selangor. This study can improve the way that flood risk is assessed and managed. It also might help in building infrastructure and flood control solutions, especially for flood-prone regions. Based on the analysis conducted across 13 streamflow stations in Selangor, the POT approach was found to outperform AM in 10 stations, indicating its effectiveness in capturing a broader range of flood events. Among the three candidate distributions, the GPA distribution is being selected at 9 out of 13 stations, particularly due to its lower MAE, RMSE, and Bias values. For instance, POT-GPA combinations at stations like Sg. Bernam At Jam. Skc, Selangor and Sg. Selangor at Rantau Panjang recorded significantly lower MAE, RMSE, and Bias values compared to GLO and GEV. GLO and GEV was selected at 2 stations at 1 station respectively, indicatin comparatively less consistent performance. These findings suggest that the POT and GPA combination provides a more reliable and accurate estimate of flood frequency in Selangor. The results of this study are to support improved flood risk assessment and infrastructure planning in Selangor and similar flood-prone areas.